(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
It has been demonstrated through multiple publications and conferences that views and professional approaches of Adapted Physical Education (APE) are changing in Hungary. Key components of the reform process are information, implementation and adaptation of the new methods. It is necessary to run research projects that can assist in broadening and supplementing the existing knowledge; assist with theoretical and practical implementation of new, innovative tools and methods. Our aim is to support this requirement through the present research project. Our goal is to get a full picture of experiences and motivation towards postgraduate education of Hungarian Adaptive Physical Educators. Adaptive Physical Educators spend 2-4 days a year in further education, regularly attend national conferences and local professional gatherings. They are motivated by professional curiosity and practical benefits of the acquired knowledge. Hydrotherapy, Fitball and Schroth therapy are the most popular choices amongst the latest tools and methods. Their practical adaptability is varied. Most Adaptive Physical Educators are interested in gaining further training in topics of spinal stabilisation, Schroth therapy, hydrotherapy and TRX. It is important to find a way to integrate these methods and tools to the day to day APE actions.